COMPARATIVE STUDY OF FLEXOR TENDON REPAIR BY MODIFIED KESSLER’S TECHNIQUE WITH OR WITHOUT USING VENOUS GRAFT AS A TENDON SHEATH SUBSTITUTE IN ZONE II - Hassan, Rebwar Abdullah; Barawi, Omer Ali Rafiq; Zangana, Ari Rahim (European Scientific Journal, ESJ, 2015)
Background: Hands are frequently exposed to injuries during daily working hours which might affect its function. Flexor tendon injuries of the hand result in loss of function. The main goal of surgery is to restore function, and avoid the occurrence of postoperative adhesions. However, a better understanding of the process of tendon healing, and continuous evolution of operative technique helps in improving the result. The use of venous graft as a tendon sheath substitute following tendon repair, reduces the adhesion formation, improves tendon nourishment, decreases the need for intensive physiotherapy, restores the function, and improves the results. Despite this remarkable progress, flexor tendon lesions still continues to present difficulty. Objectives: To observe the effectiveness of using vein graft in tendon sheath reconstruction with the aim of decreasing adhesions and comparing it to the conventional method of tendon repair. Patients and Methods: Forty patients who were injured recently, had flexor tendon injuries of the hand involving zone II. They were divided into test and control groups (20 patients each). Modified Kessler technique for primary repair of acute flexor tendons injuries were used in both groups added by the cephalic vein as a tendon sheath substitute in the test group. Results: T h e evaluation of the results is based on TAM (Total Active Motion) score of the ASSH (American Society for Surgery of the Hand). The final results were 75% excellent, 25% good, with no fair or poor results concerning the test group, while in the control group, there was no excellent results; thus, 55% good, 45% fair, and the results obtained were not poor. Conclusion: Repair of the flexor tendon injuries using modified Kessler technique using a venous graft as a tendon sheath substitute and early active movement are recommended to provide effective results as a replacement for the conventional methods.